1989
DOI: 10.1149/1.2097481
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐Oxidation of Formaldehyde on Thermally Prepared RuO2 and Other Noble Metal Oxides

Abstract: The electro-oxidation of formaldehyde has been investigated at thermally prepared noble metal oxides, especially RuO2, in aqueous solution. Studies were carried out on thin layers of oxide supported on Ta or Ti, and on thin, Teflonbonded oxide layers attached to a glassy carbon rotating disk electrode. The catalytic activity of RuO2 for HCHO oxidation was considerably greater than that of IrO2 and Rh203. At RuO2, formaldehyde was observed to undergo oxidation to formate at potentials from ca. 0.75-1.25V vs. re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 29 publications
1
24
0
3
Order By: Relevance
“…The cyclic voltammetry measurements were carried out in in 0.5 mol dm -3 H 2 SO 4 using a potentiostat (EG&G/PAR model 273). The potentials in this study are referred to the Hg/Hg 2 SO 4 /SO 4 2-(MSE) reference electrode. Acetaldehyde (CH 3 CHO > 99%) and propionaldehyde (CH 3 CH 2 CHO > 98%) were obtained from Merck and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclic voltammetry measurements were carried out in in 0.5 mol dm -3 H 2 SO 4 using a potentiostat (EG&G/PAR model 273). The potentials in this study are referred to the Hg/Hg 2 SO 4 /SO 4 2-(MSE) reference electrode. Acetaldehyde (CH 3 CHO > 99%) and propionaldehyde (CH 3 CH 2 CHO > 98%) were obtained from Merck and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…4 The majority of the work has been done with the corresponding alcohols -methanol, 5 ethanol, 6,7 as examples. Burke and Murphy described the oxidation of methanol at RuO 2 electrodes and suggested that oxidation occurred via interaction with an OH ads species at the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…The i k,L value was found to be 10.9 mA and the k h can thus be calculated as 7.99610 À4 cm=s. Similar k h value was reported for the Ru IV=VI mediated formaldehyde oxidation reaction on a thermally prepared RuO 2 electrode [33]. The order of reaction was measured by an indirect RDE electrochemical method under the reaction condition of the mixedactivation-diffusion control [18,38].…”
Section: Kinetic Analysismentioning
confidence: 61%
“…The catalytic and electrocatalytic activity strongly depend on particle size, size distribution and specific surface area of the powder, which in turn are governed by the technique used for the oxide preparation [1][2][3][4] . Traditionally, the active oxide coatings are usually prepared at about 450 ℃ by thermal decomposition of metal chloride and alkoxide coatings painted onto titanium substrates [5,6] .…”
Section: Introductionmentioning
confidence: 99%